Aeroacoustic investigation of unsteady transonic cavity flow via open CFD source codes - Fadıl, Ali Can (Graduate School, 2022)
Cavity flow research has been ongoing since the 1940s, especially for weapon bay use in fighter aircraft. With the development of acoustic analogy by Lighthill, aeroacoustic studies have also embarked on cavity flow. The studies which were firstly done for military purposes have expanded intending to reduce the aerodynamically generated noise that may disturb the comfort of the passengers and the inhabitants near the airport. As time progresses, new regulations are made on this subject and the maximum decibel limit is gradually being lowered. Hence, it is aimed to prevent noise pollution, especially in big cities. As stated above, the cavity geometry examined within the scope of the thesis can be seen in the weapon bay of warplanes, the landing gear of warplanes and passenger planes, the door cavities, sunroofs and windshield openings of automobiles. Since these flow types contain more than one phenomenon in terms of fluid mechanics discipline and their modeling is relatively effortless, they represent a fundamental problem on which intensive studies have been carried out. Modern military warplanes and unmanned warplanes tend to carry their ammunition in weapon bay embedded in the fuselage, rather than wing, to reduce the radar cross-section as much as possible and to operate without being detected by the radar systems. Flow events that occur in the weapon bay during the ammunition separation of warplanes that carry bombs and missiles in their internal weapon bay may cause the bomb not to leave the aircraft in a safe and correct trajectory, resulting in undesirable consequences and hence it is of crucial importance to understand and analyze them. Although it looks geometrically simple, cavity flows have indeed complex structures due to the effects of high velocity, pressure, density gradients, turbulence, and instability. As a result of the studies that have been read within the range of the thesis study, it was seen that the most important factor affecting the cavity flow is feedback oscillations. The shear layer is formed when the boundary layer that forms between the free stream and the surface is split from the surface at the cavity's front edge. The resultant shear layer travels along the bay, eventually colliding with the aft wall at the cavity's rear edge. The interaction occurring in this region is accepted as the main acoustic source. The acoustic waves created as a result of this interaction are known to flow towards the cavity's leading-edge, altering the boundary layer's separation period in that location. The interaction between flow-field and the aeroacoustic field is an crucial area of study. This thesis aims to examine and understand the noise caused by cavity flow and the influence of cavity door opening on pressure distribution. Within the scope of the study, a three-dimensional (3D) cavity called M219 in the literature with a L/D ratio of 5 and a W/D ratio of 1 was used, while all analyses were carried out for ReL=10x106 and ReL=13x106 and =0.85. The equations that characterize the motion of fluids called Navier-Stokes Equations want to show both parabolic and hyperbolic characteristics in the transonic region and thus it outshines as a field in which studies are intensified. Detached Eddy Simulation (DES) and Large Eddy Simulation (LES) turbulence models were used throughout the analysis. L is defined as 0.508 meters while D is 0.1016 meters. L represents the cavity length while D represents the cavity depth. Additionally, The International Standard Metric Conditions for air were used. Calculations were executed for approximately 35 convective time scale (CTS). A non-dimensional time step of 10-3 was employed for all calculations and thus it takes 1000 time steps to travel a particle along the cavity length. Pressure values were read and recorded for each time step from 10 probes placed at certain points on the cavity floor. The overall average sound pressure level (OASPL) and power spectral density (PSD) was calculated with the pressure values read and computed sound pressure level (SPL). PSD values were calculated by using Fast Fourier Transform (FFT). The comparison showed that both LES and DES results were in reasonable agreement with experimental results. Passive and active control methods can be used to reduce or control noise generation in cavity flow. Whereas passive control methods are applied by making geometric changes on the body, the energy exchange is applied in active control methods. As the shear layer – trailing edge interaction outshines as the main acoustic source, it has been seen in the literature that configurations that drop this interaction are more successful in preventing noise. Within the scope of this thesis, cavity doors are investigated as a passive control mechanism. In this thesis, OpenFOAM (Open-source Field Operation and Manipulation), an open-source computational fluid dynamics (CFD) tool based on C++ and running on Linux, was used for all calculations. Analyses were conducted on the Faculty of Aeronautics and Astronautics TAI-ITU High-Performance Cluster.
Açık kaynak CFD kodu ile zamana bağlı transonik kavitenin aeroakustik analizi
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2022
Keywords: aeroacoustic; aeroakustik; transonik uçuş; transonic flight